Factors associated with the revolving door phenomenon in patients with schizophrenia: results from an acute psychiatric hospital in Romania - Dionisie, Vlad; Puiu, Maria Gabriela; Manea, Mihnea Costin; Moisa, Emanuel; Dumitru, Ana Maria; Ibadula, Leila; Mares, Aliss Madalina; Varlam, Corina Ioana; Manea, Mirela (Frontiers in Psychiatry, 2025)
BackgroundThe revolving door phenomenon refers to patients with frequent hospital admissions and emerged after deinstitutionalization reforms have been implemented. Schizophrenia is a severe and debilitating mental disorder and has frequently been identified as one of the most prevalent disorders among revolving door patients. Therefore, this research aimed to identify socio-demographic and clinical factors associated with the revolving door phenomenon in patients with schizophrenia.MethodsWe conducted an observational and retrospective cohort study and collected data from the medical records of individuals admitted to the largest psychiatric hospital in Romania during a 2-year period. Patients with three or more admissions during a 12-month period were identified as revolving door.ResultsOf the total of 635 patients included in this study, 108 met the criteria for revolving door. Patients had a mean age of 44.55±12.83 years and most of them were single (81.7%) and receiving a disability pension (68.7%) and had an illness duration of more than 5 years (81.9%). Male gender (p=0.000), younger age (p<0.05), presence of psychiatric comorbidity (p<0.05), substance use disorder (p=0.000) and alcohol use disorder (p<0.01) were associated with the revolving door patients. A binary linear logistic regression revealed that male gender (OR=1.92, 95%CI:1.21-3.08), shorter hospitalization (OR=0.982, 95%CI:0.964-1.000), substance use disorder (OR=2.47, 95%CI:1.16-5.26), verbal (OR=1.44, 95%CI:1.05-1.98) and physical (OR=1.331, 95%CI:1.017-1.744) aggression were predictive factors for frequent use of inpatient services.ConclusionsThe results may facilitate development of future reform policies aimed at reducing the revolving door phenomenon, including implementing transitional care interventions between hospital and community services.